Molecular dissection of haustorium development in Orobanchaceae parasitic plants. Issue 3 (30th March 2021) - Furuta, Kaori Miyashima; Xiang, Lei; Cui, Songkui; Yoshida, Satoko
Abstract : Characterizing molecular aspects of haustorium development by parasitic plants in the Orobanchaceae family has identified hormone signaling/transport and specific genes as major players.